Local Environment Analysis In Urban Design Studies - Adel Said Hadi (Iraqi Journal of Architecture and Planning, 2009)
The absence of clear understanding and awareness of local urban environmentanalysis and its impact on urban design studies, in addition to the influence ofnew westemarchitectural theories and ideas, had led to the problems ofcopying and repeating urbandesign solutions by some professional architects and students .This paper discusses the impact of local environmental analysis in preparing efficienturban design projects.It aimes at clarifying the importance of carrying out urban environment field studiesto bridge the gap between theory and practice in the urban design ideology.It presents a proposed methodology to diagnose environmental problems and to findpossible solutions in the urban design projects.